Electrical transport properties of cerium doped Bi2Te3 thin films grown by molecular beam epitaxy. (December 2021) - Teng, Peng; Zhou, Tong; Wang, Yonghuan; Zhao, Ke; Zhu, Xiegang; Lai, Xinchun
Abstract: Introducing magnetism into topological insulators (TIs) can tune the topological surface states and produce exotic physical effects. Rare earth elements are considered as important dopant candidates, due to their large magnetic moments from heavily shielded 4f electrons. As the first element with just one 4f electron, cerium (Ce) offers an ideal platform for exploring the doping effect of f-electron in TIs. Here in this work, we have grown cerium-doped topological insulator Bi2 Te3 thin films on an Al2 O3 (0001) substrate by molecular beam epitaxy (MBE). Electronic transport measurements revealed the Kondo effect, weak anti-localization (WAL) effect and suppression of surface conducting channels by Ce doping. Our research shows the fundamental doping effects of Ce in Bi2 Te3 thin films, and demonstrates that such a system could be a good platform for further research.